PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS POWERPOINT BERBANTUAN MIND MAP PADA MATERI SISTEM PEREDARAN DARAH PADA MANUSIA KELAS XI SMA/MA - Syaitika, Aprillia; Fauziah, Nurul (Universitas Cokroaminoto Palopo, 2023)
The development of powerpoint-based learning media assisted by mind maps is included in research and development (R&D). min map is one of the teaching materials that makes it easy to place information into the brain and extract information from the brain during learning activities. This study aims to produce learning media based on PowerPoint assisted by a mind map on material on the human circulatory system that is valid and practical. This development research uses the Plomp development model which has three stages, namely the initial investigation stage, the development or prototyping stage, and the assessment stage. The validation results of learning media developed by media experts were 93.33% (very valid), material experts 91.38% (very valid), learning experts 98% (very valid). The result of practicality by students is 89.67% (very practical) and the result of practicality by teachers is 93.49% (very practical).